Queen Esther : [large type] a novel - Irving, John, 1942- (Thorndike Press large print top shelf., 2025)
Esther Nacht is born in Vienna in 1905. Her father dies on board a ship to Portland, Maine; her mother is murdered by anti-Semites in Portland. Dr. Larch knows it won't be easy to find a Jewish family to adopt Esther; in fact, he won't find any family who'll adopt her. When Esther is fourteen, soon to be a ward of the state, Dr. Larch meets the Winslows, a philanthropic New England family with a history of providing foster care for unadopted orphans. The Winslows aren't Jewish, but they despise anti-Semitism. Esther's gratitude for the Winslows is unending; even as she retraces her roots back to Vienna, she never stops loving and protecting the Winslows. In the final chapter, set in Jerusalem in 1981, Esther Nacht is seventy-six.